The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5851/kosfa.2017.37.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pre-Converted Nitrite from Red Beet and Ascorbic Acid on Quality Characteristics in Meat Emulsions

Abstract: We investigated the effects of fermented red beet extract and ascorbic acid on color development in meat emulsions. The pH of meat emulsions containing red beet extract decreased with an increase in the amount of extract added. The redness of the treated meat emulsions was higher than that of the control with no added nitrite or fermented red beet extract (p<0.05), though the redness of the meat emulsions treated with fermented red beet extract only was lower than in that treated with both fermented red beet e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
(45 reference statements)
3
25
1
5
Order By: Relevance
“…erefore, TBARS value was decreased over time. ese results are in agreement with those reported by Choi et al [28] who demonstrated that the TBARS value of samples treated with fermented red beet and starter culture was lower than that of the untreated samples. On the contrary, Krause et al [15] reported no significant reduction in lipid oxidation following treatment with fermented vegetable powder compared to treatment with sodium nitrite.…”
Section: Vbn and Tbars Content In Cured Pork Loinsupporting
confidence: 93%
See 4 more Smart Citations
“…erefore, TBARS value was decreased over time. ese results are in agreement with those reported by Choi et al [28] who demonstrated that the TBARS value of samples treated with fermented red beet and starter culture was lower than that of the untreated samples. On the contrary, Krause et al [15] reported no significant reduction in lipid oxidation following treatment with fermented vegetable powder compared to treatment with sodium nitrite.…”
Section: Vbn and Tbars Content In Cured Pork Loinsupporting
confidence: 93%
“…Low pH of the fermented spinach may have resulted in the low pH of the cured meat. Choi et al [28] observed a decrease in the pH of cooked meat emulsions treated with fermented red beet extract with a concomitant increase in the concentration of the extract; the pH of cooked meat emulsions showed a trend similar to that of raw meat emulsions. Sindelar et al [26] reported a similar trend in the pH of cured hams treated with vegetable juice powders.…”
Section: Changes In Ph Values and Color Of Raw Cured Pork Loinmentioning
confidence: 96%
See 3 more Smart Citations